2019
DOI: 10.3390/nu11102362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-Theanine Administration on Stress-Related Symptoms and Cognitive Functions in Healthy Adults: A Randomized Controlled Trial

Abstract: This randomized, placebo-controlled, crossover, and double-blind trial aimed to examine the possible effects of four weeks L-theanine administration on stress-related symptoms and cognitive functions in healthy adults. Participants were 30 individuals (nine men and 21 women; age: 48.3 ± 11.9 years) who had no major psychiatric illness. L-theanine (200 mg/day) or placebo tablets were randomly and blindly assigned for four-week administration. For stress-related symptoms, Self-rating Depression Scale, State-Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 58 publications
1
53
2
Order By: Relevance
“…The same 200 mg L-THE dosage is clinically reported to acutely attenuate BP (the rise seen in high-stress-response adults), as well as reducing anxiety after stress loading tasks [13]. Additionally, the findings of a relatively recent study have indicated that consumption of L-THE (200 mg) has potential to promote mental health by providing better quality sleep and improvement in cognitive functioning by improving verbal fluency and executive functioning scores [14]. Similarly, a study measuring BP [36] at time points of 20 and 70 min respectively post 97 mg L-THE and 40 mg caffeine intake, highlighted the attenuative effects L-THE has on caffeine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same 200 mg L-THE dosage is clinically reported to acutely attenuate BP (the rise seen in high-stress-response adults), as well as reducing anxiety after stress loading tasks [13]. Additionally, the findings of a relatively recent study have indicated that consumption of L-THE (200 mg) has potential to promote mental health by providing better quality sleep and improvement in cognitive functioning by improving verbal fluency and executive functioning scores [14]. Similarly, a study measuring BP [36] at time points of 20 and 70 min respectively post 97 mg L-THE and 40 mg caffeine intake, highlighted the attenuative effects L-THE has on caffeine.…”
Section: Discussionmentioning
confidence: 98%
“…The consumption of L-THE is associated with a sensation of relaxation, and is proposed to elicit acute stress-reducing effects [3] as well as providing the characteristic 'umami' flavour [6]. In addition, the consumption of L-THE is associated with antihypertensive [12,13], anti-inflammatory properties [8] as well as improvements in cognitive functioning in healthy adults [14] and when consumed in combination with caffeine [10]. Studies report stress lowering effects, expressed physiologically in the form of reductions in heart rate (HR), observed post-completion of a stress-inducing mental arithmetic task after the consumption of L-THE (200 mg) in its relatively pure form [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that 4 weeks of administration of TEA (200 mg/day) was also able to reduce stress-related symptoms and improve cognitive functions in healthy adults [ 50 ]. Moreover, TEA was reported to possess beneficial effects in the treatment of anxiety and sleep disturbance [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, theanine has been reported to have beneficial effects on depressive disorder, anxiety, sleep disorders, and cognitive decline in patients with major depressive disorder, and on stress-related symptoms and cognitive functions in healthy adults [ 35 , 46 ]. The results of our study are considered to be important clues for elucidating how theanine acts in the brain to ameliorate stress-related symptoms.…”
Section: Discussionmentioning
confidence: 99%